HAMBATAN KOMUNIKASI LINTAS AGAMA ANTAR KONFLIK UMAT BERAGAMA ISLAM DAN KRISTIANI DI DESA PANCUR BATU TUNTUNGAN - Kartika Khairana, Ahmad Fauzi (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2020)
Abstract: This study aims to find out how the Barriers to Interfaith Communication Between Religious People and the expectations of each ethnic group in maintaining the issue of harmony of inter-ethnic life in Pancur Batu which consists of the majority of Christian, Malay, and Javanese (Islamic) ethnicities. Multi-ethnic life in Pancur Batu often causes various conflicts that occur between ethnicities. This research is a qualitative research using descriptive qualitative methods. In this study the authors linked several theories of intercultural communication and identified communication barriers such as ethnocentrism, Social Prejudice and others. In this study, it was found that inter-ethnic barriers can arise due to the absence of an open mind in the face of differences, the absence of mutual tolerance and mutual respect between ethnic groups. In addition, communication barriers are also one of the factors that arise between ethnic conflicts.Keywords: Communication, Religious and cultural people, Conflict, Barriers, Harmony